The Congo plunder and resistance - Renton, David (London Zed Books, 2007)
This book traces the story of the Congo from the unleashing of King Leopard's fury across the region in the 19th century, to the Western sponsored murder of Patrice Lumumba in 1961 to the war that has ravaged the country since 1997. It is an immensely readable and radical introduction to the Congo that pays attention to the importance of economic production for social organization throughout the country's recent history. It also argues that the nature of global capitalism, far from always leading to modernization, can in fact mean the expansion of private capital accompanied by social collapse. As for the future, the hope is that another politics will emerge from the resistance of ordinary Congolese to imperialist slaughter and the post-independence Mobutu dictatorship.
Includes bibliographical references (p. [211]-231)
Keywords: Imperialism-History. Capitalism-Political aspects -History. Mines and mineral resources -Political aspects-Congo (Democratic Republic-History. Government, Resistance to-Congo (Democratic Republic)-History. Congo (Democratic Republic) -Colonial influence. Congo (Democratic Republic) -Economic conditions. Congo (Democratic Republic) -Politics and government. Congo (Democratic Republic) -History, Military